Hubungan antara Usia, Berat Badan dan Beban Kerja terhadap Kejadian Kelelahan Kerja pada Sopir Angkutan Kota (Angkot) di Kota Depok Tahun 2020 - Saputra, Aditiyana Eka; Hartono, Budi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
Fatigue is a condition of the body that can no longer carry out an activity, and can cause adverse effects if it is not treated immediately. Everyone can experience fatigue that occurs as a result of an activity or work they do. Work that is done repeatedly and has a long time to do it will certainly cause work fatigue. Public transportation drivers who work long hours and go through the same line / route will cause work fatigue. The purpose of this study was to determine the relationship between age, body weight and workload on work fatigue in public transportation drivers in Depok City. The research design was analytic survey with cross sectional design, 73 public transportation drivers as respondents were taken by random sampling in Depok Terminal. Retrieval of data using the Reaction Timer Lakassidaya 70 to measure fatigue, digital weight scales, questionnaires, digital tensimeter and data processing using the correlation test. The results showed that the average public transportation driver experienced work fatigue (389.93 milliseconds), an average age (43 years), an average body weight (63 kg) and an average workload (92 beats / minute). The results of the bivariate analysis showed that there was a significant relationship between age and fatigue (p: 0.0001) and the value of r (0.583) had a strong relationship. Weight variable with work fatigue is not related (p: 0.200) with a value of r (0.90) a weak relationship and workload with fatigue is not related (p: 0.169) with a value of r (0.153) a weak relationship. In conclusion, angkot drivers in Depok experience fatigue and age factors have a strong relationship to the occurrence of fatigue.